2019
DOI: 10.1111/jbi.13773
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the food webs of tetrapods across Europe through the prism of the Eltonian niche

Abstract: Aim: Despite recent calls for integrating interaction networks into the study of large-scale biodiversity patterns, we still lack a basic understanding of the functional characteristics of large interaction networks and how they are structured across environments. Here, building on recent advances in network science around the Eltonian niche concept, we aim to characterize the trophic groups in a large food web, and understand how these trophic groups vary across space. Location: Europe and Anatolia.Taxon: Tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 62 publications
1
53
0
Order By: Relevance
“…For each species, we gathered information on species‐specific trophic links plus a set of 11 trophic items: mushrooms, mosses/lichens, algae, detritus, seeds–nuts–grains, fruits, other plant parts, invertebrates, fish, domestic animals and faeces. These diet items could then be used as basal food items in the network (see Braga et al, 2019; O’Connor et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each species, we gathered information on species‐specific trophic links plus a set of 11 trophic items: mushrooms, mosses/lichens, algae, detritus, seeds–nuts–grains, fruits, other plant parts, invertebrates, fish, domestic animals and faeces. These diet items could then be used as basal food items in the network (see Braga et al, 2019; O’Connor et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This could yield false negatives in our dataset (i.e., interactions that exist in nature but that we characterized as non-existent because the literature fails to document those interactions). Using the approach proposed by Morales-Castilla et al (2015), it is possible to use data on species' ecology (e.g., habitat preferences) and distribution (for example considering the data presented in Maiorano et al 2013) to distinguish potential trophic links (what we reported) from trophic links actually occurring (see Braga et al 2019 andO'Connor et al 2020).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we almost can, and because we definitely should. A better understanding of species interactions, and the networks they form, would help unify the fields of community, network, and spatial ecology; improve the quantification of the functional relationships between species (Dehling and Stouffer 2018;O'Connor et al 2020); re-evaluate metacommunities in light of network structure (Guzman et al 2019); and enable a new line of research into the biogeography of species interactions (Massol et al 2017;Braga et al 2019) which incorporates a synthesis of both Eltonian and Grinnellian niche (Gravel et al 2019). Further, the ability to reliably predict and forecast species interactions would inform conservation efforts for protecting species, communities, and ecosystems.…”
Section: Conclusion: Why Should We Predict Species Interaction Network?mentioning
confidence: 99%
“…Choosing the prior knowledge that we want to give to the residual covariance matrix is tricky, but feasible. For instance, in a species-rich foodweb, there are a fair amount of species that share the same preys and predators with others, forming what is usually called trophic groups (O'Connor et al, 2020). If they are known, or inferred with a specific approach like a stochastic block model (Lee and Wilkinson, 2019), the number of trophic groups can be used as a prior to reduce the residual correlation matrix.…”
Section: Introductionmentioning
confidence: 99%